Automating Infrastructure Management: Benefits and Challenges of Ansible and Terraform Implementation Across Sectors - Avinash Pathak, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the implementation and impact of Infrastructure as Code (IaC) practices using Ansible and Terraform across various industries. Through a mixed-methods approach combining case studies, surveys, and quantitative analysis, we investigate how these tools enable more efficient, scalable, and repeatable infrastructure deployments. Our findings reveal significant benefits, including reduced operational costs (average 30% reduction), improved resource utilization (up to 40% increase), and enhanced disaster recovery capabilities (50% faster recovery times). However, challenges such as skills gaps, security concerns, and legacy system integration persist. The article provides insights into industry-specific applications, highlighting how finance, healthcare, and telecommunications sectors leverage these tools to meet unique demands. We present best practices for successful implementation, emphasizing continuous monitoring, data governance, and cross-functional collaboration. This article contributes to the growing body of literature on IaC and offers practical recommendations for organizations seeking to optimize their infrastructure management strategies in an increasingly digital landscape.
Keywords: Infrastructure as Code; Ansible, Terraform; IT Automation; Cloud Infrastructure Management